Dinamika Konflik Interpersonal antara Orang Tua dan Anak dalam Pemilihan Karier: Analisis Peran Bimbingan Karier di SMA N 2 Kupang Timur - Falukas, Linda Lidia; Taneo, Silvester; Pradana, Yoga (Pencerah, 2025)
This study explores the dynamics of interpersonal conflict between parents and students in career decision-making at SMA Negeri 2 Kupang Timur, a context characterized by strong cultural values and limited access to career information. Using a qualitative phenomenological approach, the research examines forms of conflict, contributing factors, and the emotional and academic impacts on students. Findings reveal that conflicts commonly arise from mismatched expectations, with parents prioritizing stability and social status while students seek careers aligned with personal interests and talents. These conflicts often lead to stress, decreased motivation, and strained family relationships. The study highlights the significant role of Guidance and Counseling (BK) teachers as mediators who facilitate constructive communication. Additionally, the Interest and Talent Assessment (ABM) serves as an effective tool to bridge perception gaps by providing objective data. The research concludes that reconciliation is achievable through open dialogue, data-based understanding, and collaborative decision-making involving both parents and students.